A Study on Sector Wise Comparative Analysis of NPAs of Public Sector and Private Sector Bank in India - Ms. Swati Prajapat, Dr. Nupur Ojha (International Journal of Advanced Science and Technology, 2020)
Various studies have realized that the public sector banks lacks as compared to private sector banks from the view point of NPA position. So this study carry out the sector wise comparative analysis of two banks viz., one from the public sector banks i.e. State Bank of India and Punjab National Bank and the other from the private sector banks i.e. ICICI bank and AXIS Bank. This study aim to reveal the actual sector wise NPA position of both the banks and to do their comparative analysis to identify which sector is the highest NPA making in these banks. Also this study compares the sector wise target achievement with reference to priority sector lending and their sector wise profitability. So that it will be identified that which sector of economy is non-performing for these banks.